Performance of a deep learning reconstruction method on clinical chest-abdomen-pelvis scans from a dual-layer detector CT system - Schuppert, Christopher; Rahn, Stefanie; Schnellbächer, Nikolas David; Bergner, Frank; Grass, Michael; Kauczor, Hans-Ulrich; Skornitzke, Stephan; Weber, Tim; Do, Thuy (Tomography, 2025)
Objective: The objective of this study was to compare the performance and robustness of a deep learning reconstruction method against established alte...
Online veröffentlicht am 25. August 2025
Gesehen am 16.02.2026